GUERILLA MARKETING : - Gegung, Eunike (Universitas Nusa Cendana, 2025)
Despite the expansion of research on guerrilla marketing, the concept of this practice related to SMEs needs to be scrutinized more. This article highlights the benefits of guerrilla campaigns for small and medium-sized companies. The guerrilla marketing concept revolves around unconventional tactics to obtain maximum results with minimal costs. As its nature is emphasized on unusual and creative approaches this may help companies get their brand noticed and increase visibility. It also promotes customer engagement and targets specific audiences through the concept of “you” marketing where every word and idea is about meeting customer needs and wants. However, the outcome of guerrilla campaigns can only be desirable if the content is well received by its targeted audiences. This means the campaign's success does not rely on mind-blowing ideas but rather on proper social acceptance. This study used a literature review approach to analyze research problems and generate a rationale for the issue. The data were obtained through the use of secondary sources such as documents, academic journals, textbooks, media releases, articles, and online sources to gain useful information. Keywords: Guerrilla Marketing; SMEs; Benefits